SMA, GTA and P-GMA dissimilar weld joints of 304LN stainless steel to HSLA steel; Part-2: hot corrosion kinetics. (1st August 2018) - Anant, Ramkishor; Dahiya, Jag Parvesh; Agrawal, B P; Ghosh, P K; Kumar, Ravindra; Kumar, Sudhir; Kumar, Kaushal
Abstract: A study of hot corrosion kinetics of dissimilar weld joints of 304LN austenitic stainless steel and HSLA steel, which are welded by commonly used arc welding processessuch as P-GMAW (pulsed current gas metal arc welding), GTAW (tungsten inert gas welding), and SMAW (shielded metal arc welding), has been conducted. The joints were then exposed to a molten salt environment of K2 SO4 + NaCl (50%) at 923 K (650 °C) under cyclic conditions, that is, 1 h of heating and subsequently 20 min of cooling. A gravimetric analysis was conducted and it was observed that salt-coated samples follow a parabolic rate law. SEM/EDAX, XRD, and line mapping were used to systematically characterize the resulting oxide scale in the dissimilar weld joints. The influence of the molten salt environment on the hot corrosion behavior of dissimilar welded specimens is also discussed. From the hot corrosion studies, it was concluded that the longer the duration of exposure to molten salt, the higher the weight gain by the weldment.